Cultivable fungal diversity associated with the digestive tube of stingless bees (Melipona spp.) in the Brazilian Amazonia - Almeida, Cleomara Ramos; Souza, João Raimundo Silva de; Silva, Beatriz Leite da; Giglio, Vinicius José (Acta Scientiarum. Biological Sciences, 2024)
Stingless bees interact with diverse symbiotic organisms, such as bacteria, fungi, mites and insects. We isolated and identified filamentous fungi presents in the digestive tract of stingless bees (Melipona spp.) to quantify this association and discussed their importance for the health of these insects. Twenty stingless bees were collected and their digestive tracts were analyzed. The slide micro-cultivation technique was used for morphological identification of the fungi. A total of 1,447 fungal colonies were isolated, identifying nine genera, with Aspergillus, Paecilomyces, and Cladosporium being the most prevalent. The findings highlight fungi’s diversity and potential pathogenicity, with implications for bee health and biodiversity conservation. The first record of the genus Lasiodiplodia in stingless bees (Melipona spp.) expands the knowledge about the fungal microbiota of these organisms. Although some fungal species can be harmful, understanding these interactions can promote management strategies for stingless bees.